Routine Adoption of TIMP2 and IGFBP7 Biomarkers in Cardiac Surgery for Early Identification of Acute Kidney Injury. Issue 12 (December 2017) - Levante, Chiara; Ferrari, Fiorenza; Manenti, Chiara; Husain-Syed, Faeq; Scarpa, Marta; Danesi, Tommaso Hinna; De Cal, Massimo; Corradi, Valentina; Virzì, Grazia M.; Brendolan, Alessandra; Nalesso, Federico; Bezerra, Pércia; et al.
Background and purpose: Acute Kidney Injury (AKI) is a severe complication affecting many hospitalized patients after cardiac surgery, with negative impacts on short- and long-term clinical outcomes and on healthcare costs. Recently, clinical interest has been aimed at defining and classifying AKI, identifying risk factors and developing diagnostic strategies to identify patients at risk early on. Achieving an early and accurate diagnosis of AKI is a crucial issue, because prevention and timely detection may help to prevent negative clinical outcomes and avoid AKI-associated costs. In this retrospective study, we evaluate the NephroCheck Test as a diagnostic tool for early detection of AKI in a high-risk population of patients undergoing cardiac surgery at the San Bortolo Hospital of Vicenza. Methods: We assessed the ability of the NephroCheck Test to predict the probability of developing CSA-AKI (cardiac surgery-associated AKI) and evaluated its accuracy as a diagnostic test, by building a multivariate logistic regression model for CSA-AKI prediction. Results: Based on our findings, when the results of the NephroCheck Test are included in a multivariate model its performance is substantially improved, as compared to the benchmark model, which only accounts for the other clinical factors. We also define a rule – in terms of a probability cut-off – for discriminating cases that are at higher risk of developing AKI of any stage versus those in which AKI is less likely. Conclusions: Our study has implications in clinical practice: when a Nephrocheck Test result is >0.3 ng/dL, an automated electronic alert prompts the physician to intervene by following a checklist of preventive measures.